Rekontekstualisasi Penafsiran Pangan Hindu-Buddha Sumatera : Perspektif Etnobotani Historis - Rofi Surya Aryanto; Nurul Padilah; Muhammad Farhan Ramadhan; Dwi Lani Kiranti; Stevano Timothy Yehezkiel; Ilham Budi Asmoro (Universitas Negeri Gorontalo, 2026)
The east coast of Sumatera which is synonymous with swampy areas, if often associated with palm trees, leading to narratives regarding past dietary pattern that suggest sago was a food ingredient already utilized during the Hindu-Buddhis era. The presence of local rice and the use of the term umo around Muarajambi Tmeple Compound at least sugget the possibility of other ingreidentsbeing utilized. This article draws on the results of multidisciplinary research, including ethnobiology-history, biology, and ethnolinguistics. Theses discovering opens up new opportunities for interpretation regarding dietary pattern during the Hinddu-Buddhist era on the east coast of Sumatera